Financial development and household welfare: Microevidence from Thai households - Oliver Gloede; Ornsiri Rungruxsirivorn (Verein für Socialpolitik, 2010)
We provide new micro evidence on the discussion about the relationship between financial development and welfare. Relying on the concept of local financial development our analysis focuses on three dimensions of household welfare: vulnerability to poverty, investment, and consumption smoothing. Even though we cannot find a significant effect on vulnerability, we provide evidence that financial development is correlated with higher investment and better possibilities to smooth consumption. The extent of both effects is also economically significant. Our results hold for alternative specifications and variations in the measurement of financial development.
Keywords: O16; O17; G21; 330; financial development; credit rationing; vulnerability; consumption smoothing; investment; poverty; growth